2008
DOI: 10.1016/j.jvs.2008.06.058
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of soft tissue injury and neuropathy after embolo/sclerotherapy for congenital vascular malformation

Abstract: Soft tissue injuries occurred in 11.9% of patients (68 of 573) and neuropathies occurred in 8.6% (49 of 573) after undergoing embolo/sclerotherapy. Most of these complications recovered by themselves (58.9% from soft tissue injury and 85.1% from neuropathy). Our results suggest that embolo/sclerotherapy has an acceptable incidence of soft tissue injury and neuropathy, when considering the effect that the CVM had on the quality of life before treatment, so embolo/sclerotherapy is recommended as a treatment moda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 15 publications
0
45
0
Order By: Relevance
“…41 Skin complications, including necrosis, pain and blistering, are the most common side effects occurring in 8% of patients. 40,42 Local ethanol toxicity can also cause peripheral nerve injury in 2-10% of patients. 40,43 In addition, systemic side effects can occur when concentrated ethanol makes its way into the systemic circulation.…”
Section: Capillary Malformationsmentioning
confidence: 99%
“…41 Skin complications, including necrosis, pain and blistering, are the most common side effects occurring in 8% of patients. 40,42 Local ethanol toxicity can also cause peripheral nerve injury in 2-10% of patients. 40,43 In addition, systemic side effects can occur when concentrated ethanol makes its way into the systemic circulation.…”
Section: Capillary Malformationsmentioning
confidence: 99%
“…As an alternative treatment method, embolo/sclerotherapy may be an effective modality and successful in most CVMs, in particular the diffuse and infiltrative types. We previously reported that the incidence, the susceptible types, and the outcomes for skin and soft tissue injuries of embolo/sclerotherapy in CVMs (Lee et al, 2008). This chapter reviews the general aspect of the CVMs and, based on our study, expands the incidence and treatment methods, including skin graft, in addition to the prognosis of skin and soft tissue injuries developed after embolo/sclerotherpay in patients with CVMs.…”
mentioning
confidence: 85%
“…In addition, it is unknown which types of CVMs are more susceptible to skin and soft tissue injuries and which treatment methods are the most successful for these injuries. We previously reported the incidence of skin and soft tissue injury after embolo/scleorotherapy for CVM and reviewed the prognosis according to the treatment modalities in patients with skin and soft tissue injuries (Lee et al, 2008). This chapter, based on our study, has described the outcomes according to treatment methods in patients with skin and soft tissue injuries developed after embolo/sclerotherapy.…”
Section: Congenital Vascular Malformations: Skin and Soft Tissue Injumentioning
confidence: 98%
“…johann et al 3 said that sclerotherapy is safe, less invasive, with low risk of hemorrhage and cost effective. common complications are pain, swelling, redness and burning, lee et al 9 mentioned that these complications are considered acceptable when compared to its effect on quality of life. Most complications are the result of extravasation of the sclerosant.…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…Surgical Management:-Surgical management is indicated as a definitive treatment of any type of AVM and complete excision of the nidus of AVMs is possible with least chances of recurrence 9,12,13,19 . complete resection was used in the treatment of AVM in the soft tissue, such as the lip and cheek.…”
mentioning
confidence: 99%